The Influence of Digital Literacy Skills and KKG Program on Primary School Teacher Performance through Teacher Work Professionalism in Gugus 01 Raja Indragiri - Sayuti, Wahyu Alfitrah; Ningsih, Dewita Suryati; Tarigan , Mida Aprilina (West Science Business and Management, 2025)
This research aims to determine the influence of Digital Literacy Skills and KKG Program on primary school Teacher Performance through Teacher Work Professionalism in Gugus 01 Raja Indragiri. The population in this study were all elementary school teachers who joined Gugus 01 Raja Indragiri. The sampling technique used in this research was a saturated sampling technique so that the number of samples used was 56 respondents. The data analysis method in this research uses the Structural Equation Modeling - Partial Least Square (SEM-PLS) analysis method with SmartPLS version 4.0 software. The research results show that (1) Digital Literacy Skills has a significant effect on Work Professionalism, (2) The KKG Program has a significant effect on Work Professionalism, (3) Digital Literacy Skills has a significant effect on Teacher Performance, (4) The KKG Program has a significant effect on Teacher Performance, (5) Professionalism Work has a significant effect on Teacher Performance, (6) Digital Literacy Skills has a significant effect on Teacher Performance through Work Professionalism, (7) The KKG Program has a significant effect on Teacher Performance through Work Professionalism.